GDF11 slows excitatory neuronal senescence and brain ageing by repressing p21 - Di-Xian Wang; Zhao-Jun Dong; Sui-Xin Deng; Ying-Ming Tian; Yu-Jie Xiao; Xinran Li; Xiao-Ru Ma; Liang Li; Pengxiao Li; Hui-Zhong Chang; Longqi Liu; Fan Wang; et al. (Nature Communications, 2023)
Abstract As a major neuron type in the brain, the excitatory neuron (EN) regulates the lifespan in C. elegans. How the EN acquires senescence, however, is unknown. Here, we show that growth differentiation factor 11 (GDF11) is predominantly expressed in the EN in the adult mouse, marmoset and human brain. In mice, selective knock-out of GDF11 in the post-mitotic EN shapes the brain ageing-related transcriptional profile, induces EN senescence and hyperexcitability, prunes their dendrites, impedes their synaptic input, impairs object recognition memory and shortens the lifespan, establishing a functional link between GDF11, brain ageing and cognition. In vitro GDF11 deletion causes cellular senescence in Neuro-2a cells. Mechanistically, GDF11 deletion induces neuronal senescence via Smad2-induced transcription of the pro-senescence factor p21. This work indicates that endogenous GDF11 acts as a brake on EN senescence and brain ageing.